Identification of stress levels of pre-clinical students in facing the final semester block examination at the Faculty of Dentistry, Baiturrahmah University: Identifikasi tingkat stres mahasiswa pre-klinik dalam menghadapi ujian blok semester akhir pada Fakultas Kedokteran Gigi Universitas Baiturrahmah - Khusnul Khotimah; Leny Sang Surya; Satria Yandi (Makassar Dental Journal, 2024)
Stress is a condition that can be caused by uncontrolled physical demands, environment and social situations. Pressure in academic matters is one of the main causes of stress among students, such as the desire to get high grades, excessive anxiety in avoiding failure. Different people have different conditions to deal with the challenges and problems they face. The instrument used to determine the level of stress, namely the depression anxiety stress scale questionnaire (DASS-42), which includes 3 sub-variables including physical, emotional/psychological and behavioural. The purpose of this study was to determine the stress level of pre-clinical students in facing the final semester block exam at the Faculty of Dentistry, Baiturrahmah University. Descriptive research with cross sectional design was conducted at the Faculty of Dentistry, Baiturrahmah University in November 2023, purposive sampling obtained 45 samples. As a result, most experienced moderate stress levels as many as 13 respondents (28.9%) and the least experienced severe stress levels as many as 6 respondents (13.3%). It was concluded that stress can occur when a person gets demands that exceed their abilities.